Isothermal vapor liquid equilibrium measurements for difluoromethane (R32) + fluoroethane (R161) + trans-1, 3, 3, 3-tetrafluoropropene (R1234ze(E)) ternary mixtures. (July 2017) - Hu, Xiaozhen; Yang, Tao; Meng, Xianyang; Wu, Jiangtao
Highlights: Experimental measurement of VLE data for R32 + R161 + R1234ze(E) by a quasi-static analytical apparatus. The ternary system of R32 + R161 + R1234ze(E) is a zeotropic system within 283.15 to 323.15 K. Experimental data show good agreement with the predicted results of PRSV + WS + NRTL model. Abstract: Difluoromethane (R32) + fluoroethane (R161) + trans-1, 3, 3, 3-tetrafluoropropene (R1234ze(E)) ternary system could be a promising alternative refrigerant mixture. The vapor liquid equilibrium (VLE) data for this system are important for the evaluation of its performance. In this work, the VLE of R32 + R161 + R1234ze(E) were measured for the first time by a quasi-static analytical apparatus over the temperature range of 283.15 to 323.15 K. The ternary system of R32 + R161 + R1234ze(E) is a zeotropic system within the studied temperature range. The Peng–Robinson–Stryjek–Vera (PRSV) equation of state combined with the Wong–Sandler (WS) mixing rule and the non-random two-liquid (NRTL) activity coefficient model was used to predict the ternary VLE data by using the parameters of binary mixtures (R32 + R161, R32 + R1234ze(E) and R161 + R1234ze(E)). The calculated values show excellent agreement with the experimental results. The average absolute deviation (AAD) of pressure is 0.16%. The average absolute deviations of vapor phase mole fractions for R32 and R161 are 0.0021 and 0.0028, respectively.